INTELLIGENCE AND SECURITY STRUCTURES IN YUGOSLAVIA DURING WORLD WAR II - Lazić, Radojica S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: The development of intelligence and security structures in Yugoslavia in World War II was done in extremely complex political and security conditions. After the April war and signing the surrender on April 17, 1941, the Ministry of Internal Affairs of the Kingdom of Yugoslavia continued to operate within the royal government which was in exile.After the occupation, Yugoslavia was torn apart by the German and Italian forces and their allies and quislings. The territory of the country was torn into two different spheres of interest - German and Italian, as well as four areas of occupation: German, Italian, Hungarian and Bulgarian. This went on until Italy surrendered in 1943. The members of the Croatian Ustaša movement announced the forming of the Independent State of Croatia (NDH), which initially included the territories of Croatia and Bosnia and Herzegovina, and from October 1941, the territory of Srem with the city of Zemun.This paper looks at the work of intelligence and security institutions on the territory of the occupied state at the time, with a special reflection on the development of the safety organs of the partizan movement.
Keywords: Keywords: World War II, the Kingdom of Yugoslavia, safety structures, the chetnik movement, partizan movement, ally missions, the Department for People's Protection